Threat from peers: The effect of leaders’ voice endorsement on coworkers’ self-improvement motivation - Liu, Pan; Li, Daiheng; Zhang, Xiaoyan (Frontiers in Psychology, 2022)
Existing studies mainly explore the antecedents of voice endorsement and its distal outcomes on voicers themselves. However, few have examined the mechanism of leaders’ voice endorsement on the voicers’ coworkers. Drawing on the self-evaluation maintenance theory, this paper uses perceived status threat as the mediator and trait competitiveness as the moderator to construct a conceptual model to explore the effect of leaders’ voice endorsement on coworkers’ self-improvement motivation. Through an empirical study with 279 sets of questionnaires from a manufacturing enterprise in China, the results show that leaders’ voice endorsement has a positive effect on coworkers’ self-improvement motivation through coworkers’ perceived status threat and that coworkers’ trait competitiveness can strengthen the positive relationship between leaders’ voice endorsement and coworkers’ perceived status threat. In addition, coworkers’ trait competitiveness can strengthen the indirect effect of leaders’ voice endorsement on coworkers’ self-improvement motivation via coworkers’ perceived status threat. The theoretical and practical implications of these findings are discussed.